Evidence for a KATP Channel in Rough Endoplasmic Reticulum (rerKATP Channel) of Rat Hepatocytes. - Sajjad Salari; Maedeh Ghasemi; Javad Fahanik-Babaei; Reza Saghiri; Remy Sauve; Afsaneh Eliassi (PLoS ONE, 2015)
We report in a previous study the presence of a large conductance K+ channel in the membrane of rough endoplasmic reticulum (RER) from rat hepatocytes incorporated into lipid bilayers. Channel activity in this case was found to decrease in presence of ATP 100 µM on the cytoplasmic side and was totally inhibited at ATP concentrations greater than 0.25 mM. Although such features would be compatible with the presence of a KATP channel in the RER, recent data obtained from a brain mitochondrial inner membrane preparation have provided evidence for a Maxi-K channel which could also be blocked by ATP within the mM concentration range. A series of channel incorporation experiments was thus undertaken to determine if the ATP-sensitive channel originally observed in the RER corresponds to KATP channel. Our results indicate that the gating and permeation properties of this channel are unaffected by the addition of 800 nM charybdotoxin and 1 µM iberiotoxin, but appeared sensitive to 10 mM TEA and 2.5 mM ATP. Furthermore, adding 100 µM glibenclamide at positive potentials and 400 µM tolbutamide at negative or positive voltages caused a strong inhibition of channel activity. Finally Western blot analyses provided evidence for Kir6.2, SUR1 and/or SUR2B, and SUR2A expression in our RER fractions. It was concluded on the basis of these observations that the channel previously characterized in RER membranes corresponds to KATP, suggesting that opening of this channel may enhance Ca2+ releases, alter the dynamics of the Ca2+ transient and prevent accumulation of Ca2+ in the ER during Ca2+ overload.